EDUKASI DAN WORKSHOP HILIRISASI PRODUK GAMBIR (Uncaria gambir) DAERAH TALUAK TIGO SAKATO PESISIR SELATAN - Vani, Ade Teti; Dessy Abdullah; Nadia Purnama Dewi; Irwan Triansyah; Aryaldy Zulkarnaini; Yanti Fitri Yasa (Nusantara Hasana Journal, 2025)
Gambir is a plant that has high economic value and antioxidant effects. Gambir leaves contain catechins as antioxidants. Suboptimal management of gambir weakens the economic value of gambir and has not achieved optimal antioxidant effects. The purpose of community service is to provide education and workshops on making gambir tea so that optimization of gambir management is achieved. This community service consists of three steps, namely problem discovery, education on making gambir tea and workshops on making gambir tea. The results of community service activities are in the form of problem discovery, optimization of gambir products in the form of gambir tea. The results of community service are that the community agrees to optimize gambir management by conducting education and workshops on making gambir tea which are attended by the village head and the Taluak Tigo Sakato Nagari apparatus. The conclusion of community service activities is that the Taluak Tigo Sakato community agrees to optimize gambir management by making gambir tea which goes through the stages of picking, washing, drying, grinding and packaging. The packaging chosen is the use of tea bags.